2019
DOI: 10.1530/ec-19-0373
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation analysis of negative pressure therapy effect in diabetic foot ulcers

Abstract: ObjectiveNegative pressure wound therapy (NPWT) has been used to treat diabetic foot ulcerations (DFUs). Its action on the molecular level, however, is only partially understood. Some earlier data suggested NPWT may be mediated through modification of local gene expression. As methylation is a key epigenetic regulatory mechanism of gene expression, we assessed the effect of NPWT on its profile in patients with type 2 diabetes (T2DM) and neuropathic non-infected DFUs.MethodsOf 36 included patients, 23 were assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…We found that negative pressure treatment downregulated XIST in MTB‐infected RAW264.7 cells and hMDMs by regulation of XIST promoter methylation. Previous work showed an association between negative pressure treatment and DNA methylation in diabetic foot ulcers 39 . We have now revealed that negative pressure treatment activates the NF‐κB pathway by downregulation of A20, which is miR‐125b‐5p‐targeted, through decreasing XIST expression.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…We found that negative pressure treatment downregulated XIST in MTB‐infected RAW264.7 cells and hMDMs by regulation of XIST promoter methylation. Previous work showed an association between negative pressure treatment and DNA methylation in diabetic foot ulcers 39 . We have now revealed that negative pressure treatment activates the NF‐κB pathway by downregulation of A20, which is miR‐125b‐5p‐targeted, through decreasing XIST expression.…”
Section: Discussionmentioning
confidence: 62%
“…Previous work showed an association between negative pressure treatment and DNA methylation in diabetic foot ulcers. 39 We have now revealed that negative pressure treatment activates the NF-κB pathway by downregulation of A20, which is miR-125b-5p-targeted, through decreasing XIST expression. The critical regulatory role of negative pressure wound therapy on plasma miRNA expression has been highlighted recently.…”
Section: Discussionmentioning
confidence: 89%
“…In our previous reports, we saw that NPWT altered the local gene expression involved with wound healing [4]. Moreover, we showed that NPWT's action is mediated through epigenetic alterations resulting mainly in the inhibition of complement system activation [5]. In a very recent study, NPWT increased the number of circulating endothelial progenitor cells in ischemic foot ulcers of diabetic patients which was attributed to the upregulation of systemic and local vascular endothelial growth factors and stromal cell-derived factor-1 α levels [28].…”
Section: Discussionmentioning
confidence: 99%
“…Negative pressure wound therapy (NPWT) has been used as an adjunct treatment for DFUs. Its potential influence on local gene expression and epigenetic methylation in the wound bed has been recently described [4, 5]. However, NPWT's novel mechanism of action may be associated with processes involving the entire organism where signals are transmitted via circulating molecules between the organism's tissues and organs.…”
Section: Introductionmentioning
confidence: 99%
“…When applied to wounds, closure is significantly accelerated, an effect that appears to be regenerative in nature through the activation of a plethora of neurodevelopmental genes 105 . Besides pharmacological modulation, even the application of negative pressure can induce local changes in wound bed methylation thereby activating the wound healing response 107 . Could methylation therefore be a useful target in the wound healing armamentarium?…”
Section: Micrornasmentioning
confidence: 99%